Analysis of physico-chemical variables and their influence on water quality of the Bogota River using data mining. (2018) - Rojas, Jairo; Forero, Julián; Gaona-García, Paulo Alonso; Marin, Carlos Enrique Montenegro; Crespo, Rubén González
Variation of the flow rate and the concentration of different elements within a flow of water in a river must be important factors for the discovery of patterns of behaviour and predictive in terms of space and time models. Based on this, this article presents data analysis carried out based on a historical compendium of measurements on the Bogota River between the years 2008-2015, given in the results of the campaigns of monitoring provided by the Regional Autonomous Corporation CAR, through the scan tool Weka and data the use of J48 algorithm for the generation of decision trees in order to establish the influence of the physical and chemical variables in the water quality of this source, within a process of identification and interpretation at the environmental level of these factors.